ความชุกของภาวะซึมเศร้าและปัจจัยที่เกี่ยวข้องในผู้ป่วยนอกโรคจิตเภทเรื้อรัง สถาบันจิตเวชศาสตร์สมเด็จเจ้าพระยา - ปรียนันท์ สละสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To examine the prevalence of depression and associated factors of 150 chronic ambulatory schizophrenic patients of Somdet Chaopraya Institute of Psychiatry. The interview was used for demographic data, brief psychiatric rating scale, social support rating scale, life stress event scale while self reported questionnaires was used for The Zung self-rating depression scale. The SPSS for Windows was used for descriptive and inferential statistical analysis. Descriptive statistics were presented as percentage, mean, standard deviation, while inferential statistics were done for chi-square test, t-test, one-way ANOVA, Pearson s product moment correlation coefficient. Stepwise multiple regression analysis was performed to determine for significant predictive factors. The result of this study was found that prevalence of depression was 36%. Age and social support were negatively correlated to depression (p<.05 and p<.001 respectively). On the other hands, life stress events was positively correlated to depression (p<.05). In conclusion, lack of social support, young age and extrapyramidal side effects are significantly factors in prediction of depression for these studied sample.